THE FACTOR ANALYSIS OF PRONUNCIATION IN JOHN’Y'S VLOG COMMUNICATION: PHONOLOGY ANALYSIS - Nurul Aini; Muhammad Reza Pahlevi; Yuna Tresna Wahyuna (PROJECT (Professional Journal of English Education), 2024)
Many people do not speak English as their first language. It is possible that they perceive various sounds differently because the languages have different phonological features. This study is aimed to find out the process of phonological in mispronunciation and the factors of phonological that caused the mispronunciation. The elements of linguistics that being analyzed are the sounds in NCT Johnny’s vlogs named Shopping at IKEA & Assembling a Rack and 3rd Ep of Johnny’s Communication Center (JCC). The researcher collects the data by listening to all the conversations spoken by Johnny NCT in his YouTube vlogs videos. All of the words that are mispronounced are listed down and then being transcribed into phonetics transcriptions. the researcher found 25 data of mispronunciation words in Johnny's Communication Center (JCC) vlog. The type of mispronunciation words consists of  5 consonant’s mispronunciation and 20 vowels’ mispronunciation. There are three kinds of mispronunciation based on the phonological process, they are deletion, substitution, and insertion. Furthermore, based on the results of interviews conducted by researchers, four factors influence Johnny's pronunciation errors, namely mother tongue, exposure, language identity, and ego, as well as motivation and concern for sound pronunciation.